2010
DOI: 10.1074/jbc.m110.165894
|View full text |Cite
|
Sign up to set email alerts
|

Affinity, Avidity, and Kinetics of Target Sequence Binding to LC8 Dynein Light Chain Isoforms

Abstract: LC8 dynein light chain (DYNLL) is a highly conserved eukaryotic hub protein with dozens of binding partners and various functions beyond being a subunit of dynein and myosin Va motor proteins. Here, we compared the kinetic and thermodynamic parameters of binding of both mammalian isoforms, DYNLL1 and DYNLL2, to two putative consensus binding motifs (KXTQTX and XG(I/V)QVD) and report only subtle differences. Peptides containing either of the above motifs bind to DYNLL2 with micromolar affinity, whereas a myosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 58 publications
(111 reference statements)
6
58
1
1
Order By: Relevance
“…2 and 3), establishing several backbone hydrogen bonds and side chain interactions with the ␤3 strand of one of the LC8 subunit. The only interaction of the peptide with the opposite subunit of the LC8 homodimer is mainly established by Gln 947 from the highly conserved KXTQTX motif, with its side chain buried in a hydrophobic pocket formed by Ile 34 , Glu 35 , and Lys 36 from the ␣2 helix.…”
Section: Circular Dichroism Experiments On Lc8 Binding To the Nek9mentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3), establishing several backbone hydrogen bonds and side chain interactions with the ␤3 strand of one of the LC8 subunit. The only interaction of the peptide with the opposite subunit of the LC8 homodimer is mainly established by Gln 947 from the highly conserved KXTQTX motif, with its side chain buried in a hydrophobic pocket formed by Ile 34 , Glu 35 , and Lys 36 from the ␣2 helix.…”
Section: Circular Dichroism Experiments On Lc8 Binding To the Nek9mentioning
confidence: 99%
“…Only a few LC8 partners contain non-canonical binding motifs lacking the most conserved Gln residue (25). The binding affinity of LC8 to monomeric peptides is moderately weak (K d between 0.1 and 40 M) (13); however, bivalent peptides linking two consensus motifs have been shown to increase significantly the binding affinity for LC8 (34), indicating the importance of the dimer-dimer interaction in the complex of LC8 with protein partners. Despite the strong conservation in the LC8 binding region, recent biophysical data indicates an inherent plasticity that allows the interaction with these different consensus motifs (24).…”
mentioning
confidence: 99%
“…The IC84-143 segment contains the highly conserved "TQT box" and binding to LC8 caused broadening below detection limit of the peaks belonging to the residues involved in binding; a similar broadening effect that was observed for M L , while the peaks of the residues outside the binding sequence remained unperturbed and maintained the disorder state outside the binding region. On the contrary here we show not only the partial folding of the unbound M L , but also the structural transition into a β-sheet upon interaction with DYNLL2, an example of structural plasticity in a short linear motif (Figure 7).Previously we have shown by kinetic studies that the binding of DYNLL isoforms to their various partners can be best described by a conformational selection model (18). The region of the free myo5a peptide contains an inherent α-helix that should be in the unfolded state in order to fit into the binding groove of DYNLL2; this finding is consistent with a conformational selection mechanism for the formation of DYNLL complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of DYNLL2 stabilizes the flanking coiled-coil sequences (16,17). Detailed kinetic and thermodynamic characterization of this interaction using monoand dimeric myo5a fragments revealed that the dissociation constant is somewhat weaker than that of the canonical motifs(~1-5 M for a monomeric peptide) andbivalency of the ligand leads to pronounced avidity (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation